Penerapan pembelajaran stad (student team achievement division) berbantuan media komik untuk meningkatkan keterampilan pemecahan masalah materi analisis data peserta didik kelas v sd - Arfika Aulia Agustina; Matsuri Matsuri (Universitas Sebelas Maret, 2025)
This research aims to: 1) explore the implementation of the Student Team Achievement Division (STAD) learning model integrated with comic media to develop problem-solving skills in data analysis for fifth-grade students at SD Negeri Banyuanyar 1; and 2) enhance students’ problem-solving abilities in data analysis through the STAD model assisted by comic media. The study adopts a Classroom Action Research (CAR) approach, involving the classroom teacher and 28 students as participants. Data were gathered through observation, interviews, documentation, and tests, with triangulation employed to ensure data validity. An interactive data analysis method was used throughout the research. The results show a consistent improvement in students’ problem-solving performance, with the average score increasing from 50 in the pre-action stage to 68 in the first cycle, and further to 84 in the second cycle. Classical completeness also improved, rising from 32% during the pre-action phase to 68% in cycle 1, and reaching 86% in cycle 2. The study concludes that: 1) the STAD learning model combined with comic media is feasible and can be implemented effectively; and 2) the model significantly improves fifth-grade students’ problem-solving skills. Theoretically, the findings offer valuable insight into the integration of STAD and comic media within mathematics instruction. Practically, the use of comic media in the STAD model demonstrates clear benefits and positive impacts, serving as a useful reference for future educational research.This research aims to: 1) explore the implementation of the Student Team Achievement Division (STAD) learning model integrated with comic media to develop problem-solving skills in data analysis for fifth-grade students at SD Negeri Banyuanyar 1; and 2) enhance students’ problem-solving abilities in data analysis through the STAD model assisted by comic media. The study adopts a Classroom Action Research (CAR) approach, involving the classroom teacher and 28 students as participants. Data were gathe